REDD1 deletion and treadmill running increase liver hepcidin and gluconeogenic enzymes in male mice - David E. Barney; Bradley S. Gordon; Stephen R. Hennigar (Journal of Nutritional Science, 2023)
The iron-regulatory hormone hepcidin is transcriptionally up-regulated by gluconeogenic signals. Recent evidence suggeststhat increases in circulating hepcidin may decrease dietary iron absorption following prolonged exercise, however evidence is limited on whether gluconeogenic signals contribute to post-exercise increases in hepcidin. Mice with genetic knockout of regulated in development and DNA response-1 (REDD1) display greater glycogen depletion following exercise, possibly indicating greater gluconeogenesis. The objective of the present study was to determine liver hepcidin, markers of gluconeogenesis and iron metabolism in REDD1 knockout and wild-type mice following prolonged exercise. Twelve-week-old male REDD1 knockout and wild-type mice were randomised to rest or 60 min treadmill running with 1, 3 or 6 h recovery (n = 5–8/genotype/group). Liver gene expression of hepcidin (Hamp) and gluconeogenic enzymes (Ppargc1a, Creb3l3, Pck1, Pygl) were determined by qRT-PCR. Effects of genotype, exercise and their interaction were assessed by two-way ANOVAs with Tukey's post-hoc tests, and Pearson correlations were used to assess the relationships between Hamp and study outcomes. Liver Hamp increased 1- and 4-fold at 3 and 6 h post-exercise, compared to rest (P-adjusted < 0⋅009 for all), and was 50% greater in REDD1 knockout compared to wild-type mice (P = 0⋅0015). Liver Ppargc1a, Creb3l3 and Pck1 increased with treadmill running (P < 0⋅0001 for all), and liver Ppargc1a, Pck1 and Pygl were greater with REDD1 deletion (P < 0⋅02 for all). Liver Hamp was positively correlated with liver Creb3l3 (R = 0⋅62, P < 0⋅0001) and Pck1 (R = 0⋅44, P = 0⋅0014). In conclusion, REDD1 deletion and prolonged treadmill running increased liver Hamp and gluconeogenic regulators of Hamp, suggesting gluconeogenic signalling of hepcidin with prolonged exercise.